Effect of ultraviolet and x-ray radiation on optical properties of epoxy polymers dyed with organic phosphors - Laurinas, V.Ch.; Kasymov, S.S.; Yurov, V.M.; Eremin, E.N.; Vedyashkin, M.V. (Institute of Physics Publishing, 2017)
Highly purified industrial bisphenol and cycloaliphatic epoxy oligomers of ED-24 and UP-612 brands were used to produce optically transparent products. UV radiation of a lowpressure mercury lamp with 80% of the light energy at 254 nm was used to study photodegradation. X-ray apparatus with 0.7BSV-Ag tube was used as an ionizing radiation source to investigate the effect of X-rays on the spectra of organic dyes in epoxy polymer. The threshold value of the energy generated by ruby laser which indicated the degradation in the test samples recorded by light scattering method was determined to study radiation resistance of epoxy polymers. Basically, all the dyes exhibited high resistance to UV light. The observation of the absorption spectra showed that on average, a third of the dye molecules in the matrix experienced photobleaching within 200 hour exposure. The exception was coumarin 1, which was completely decolourized after 40 hours of exposure. X-ray irradiation of the samples for two hours results in the change in the optical density equivalent to that caused by 40 hour exposure to UV irradiation. However, in the first case, the matrix optical density is proportional to the irradiation time, and in the second case, it remains stable upon further UV irradiation. The comparison of photoaging processes in dyed and undyed epoxy polymers showed that the investigated organic dyes do not have a sensitizing effect on the matrix. The stability of the optical properties of the epoxy matrices exposed to the effects of different factors was found to depend on the nature of epoxy polymer and the technique of its production. The results of these effects are significantly different in the character of the change in the optical density and mechanisms of chemical transformations in polymer.